ANALYSIS OF THE STRUCTURE OF CRIMINAL ORGANIZATIONS (Annual of the Faculty of Philosophy in Skopje, 2014)
In contemporaiy surrounding, criminal structures are based on organizational models that allow growing professionalism and ejficiency. These organizational models are mostly formed by functional and principles of market, building criminal networks that are tailored to the needs of the action of the criminal market and economic processes.This paper examines structural changes in criminal organizations that may have different security implications of national securityOrganizational analysis of criminal structures enables better understanding on the advantages and disadvantages of the object of criminal processing, which allows identification of weak points of the analyzed criminal organization.